Pengaruh Pemberian Persembahan terhadap Pelayanan dan Kemajuan Kerohanian Anggota Jemaat - Tambunan, Tanjung; Sinaga, Janes; Sinambela, Juita (JUITAK: Jurnal Ilmiah Teologi dan Pendidikan Kristen, 2024)
Discussion of offerings cannot be separated from the Bible. In the Bible there are teachings about offerings that are worthy before God in both the Old and New Testaments, but does the giving of offerings have an effect on the progress of ministry and the spirituality of church members? The aim of the research is to find out, analyze, explore and test the description of the giving of offerings as well as the ministry and the spiritual progress of church members. Obtaining the influence of giving offerings on ministry, as well as the influence of giving offerings and serving on the spiritual progress of church members. This study uses a descriptive qualitative method, by analyzing and explaining the effect of offerings on the progress of ministry and the spirituality of Congregational Members. To be able to carry out effective evangelism, everything must be supported by the power of funding, this can be done through the calling of sacrifice to give offerings. Offerings are a means of funding evangelism to make it more effective. In this case all church members can be involved, and this affects the progress of ministry and spiritual growth.